Climate Change Communication and Engagement With Older People in England - Latter, Briony (Frontiers in Communication, 2022)
Although an important and influential demographic, older people have largely been forgotten about in the field of climate change communication and engagement. Despite the United Kingdom (UK) having an ageing population, little is known about how best to involve them in the climate conversation. Based on Climate Outreach’s Narrative Workshop methodology, this research contributes towards addressing this gap in the literature by providing some evidence towards what language, values and framing could work well with older people in England, as well as areas to potentially avoid and explore further. The findings of this research demonstrate the importance of community, consideration, responsibility and an international outlook to the research participants, as well as their views that governments and organisations hold important power in relation to climate change.